THE FIRE RESISTANCE AND FIELD TEST OF TREATED Maesopsis eminii WOOD WITH BORON PRESERVATIVE, VEGETABLE OILS, AND HEATING - Priadi, Trisna; Badruzzaman, Muhammad Hilmy (Association of Indonesian Forestry and Environment Researchers and Technicians, 2025)
Boric acid can be combined with vegetable oil treatment to enhance wood preservation. This research aimed to evaluate the fire resistance and above-ground field test of treated manii (Maesopsis eminii Engl.) wood with boric acid, vegetable oils, and heating. Manii wood samples were impregnated sequentially with boric acid solution and vegetable oils (neem, tamanu, and candlenut) in a tank at a pressure of 7 kg cm−2 for 4 hours at room temperature, ±26ºC. The subsequent heat treatment was at 60ºC, 120ºC, and 180ºC under atmospheric pressure for 4 hours. The fire resistance was evaluated based on sample weight loss after burning with a heating torch at 180°C ± 5°C for 4 minutes. The above-ground field test of woods was conducted on a shelf with a slope of 45º for 90 days. The results revealed that the combination of boric acid and vegetable oils treatment had better fire resistance than boric acid treatment and the control of manii wood. In the above-ground field test, the combination of boric acid and vegetable oils treatment also resulted in less weight loss due to weathering and fungal attacks. Moreover, the moisture content change was less than that of the boric acid treatment and the control samples. However, oil treatment caused a higher color change than the control samples during the field test.